NURSING STUDENTS’ PERCEPTION TO THE NECESSITY OF ENGLISH FOR SPECIFIC PURPOSES (ESP) COURSE - Suramto - suramto; Susmini Susmini; Episiasi Episiasi (LP4MK STKIP PGRI Lubuklinggau, 2021)
ABSTRACT English for Specific Purposes (ESP) has been learned and become required course for nursing students. The students’ necessity of English is essential for those learners who would like to reach the best achievement and get ready for use in the job area. The objective of this research was to determine nursing students’ perception in regard with the necessity for ESP materials at Politeknik Kesehatan Palembang Nursing Study Prorgam Lubuklinggau. The research method was conducted in quantitative survey. The participants of the research were 34 students. The data used of this research were questionnaire items and students’ responses. The data were analyzed by using SPSS version 20.0. The results of the research showed that there are 8 assignments necessity in listening skills, 11 assignments necessity in speaking skills, 7 assignments necessity in writing skills, and 6 assignments necessity in reading skills. The finding of research can be concluded that both listening and speaking skills are influential necessity for nursing students. Hence, listening and speaking skills should be mastered to fulfill students’ necessity Keywords: Nursing students, ESP, Necessity analysis